Long-Lasting Obesity Predicts Poor Work Ability at Midlife: A 15-Year Follow-Up of the Northern Finland 1966 Birth Cohort Study. Issue 12 (December 2015) - Nevanperä, Nina; Ala-Mursula, Leena; Seitsamo, Jorma; Remes, Jouko; Auvinen, Juha; Hopsu, Leila; Husman, Päivi; Karppinen, Jaro; Järvelin, Marjo-Riitta; Laitinen, Jaana
Abstract : Objective: To investigate the effect of adulthood obesity on work ability in early midlife during a 15-year follow-up. Methods: The study population included men and women ( n = 5470), born in northern Finland in 1966. Participants evaluated their current perceived work ability compared with their lifetime best at the age of 46. Participants' weight and height were measured at 31 years and self-reported at 46 years, and body mass indexes were calculated. Results: Obesity at both ages, and developing obesity between the ages of 31 and 46 increased the relative risk of poor work ability at 46 years among sexes, and among those in both low and high physically strenuous work. Conclusions: Long-term obesity and developing obesity in mid-adulthood increase the risk of poor work ability. Thus, the promotion of healthy behaviors by policies, healthcare services, and at workplaces is important.